Knowledge, attitudes, and uptake of mental health services by secondary school students in Gweru, Zimbabwe - Khombo, Sibusiso; Khombo, Kennedy; Stoddart, Robert Shalom; Sifelani, Innocent; Sibanda, Theresi (Frontiers in Psychology, 2023)
Introduction The study sought to investigate and examine knowledge, attitudes, and uptake of mental health services by secondary school students in the Gweru district. Methods Using a qualitative approach, 15 students from three secondary schools in Gweru were purposively sampled for inclusion in this study. Data collection was through semi-structured interviews. The study utilized thematic data analysis and the following themes emerged from the study; ignorance, misinformation, indifference, lack of trust, gender differences, and alternative support. Results Generally, the research findings revealed that most secondary school students were aware of the existence of mental health services although they had distorted information on the same. Poor utilization of services was largely attributed to the consideration of “formal” mental health services as the last resort for remedy after the failure of “informal” services to yield positive results. Thus, mental health services were not on the priority list of intervention measures used by secondary students in light of mental health issues. The study recommends psycho-education sessions to promote the utilization of mental health services by secondary school students. Discussion Notably, the current study revealed that participants lacked correct information about MHS and its related utility. Munson et al. (2009) concur by stating that some adolescents believed that their mental health challenges such as mood disorders were chronic, and as such, they thought that any form of intervention could not control or remedy their illness.